2012
DOI: 10.1105/tpc.111.093781
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Arabidopsis Cyclophilin38 Reveals a Previously Uncharacterized Immunophilin Fold and a Possible Autoinhibitory Mechanism

Abstract: Cyclophilin38 (CYP38) is one of the highly divergent cyclophilins from Arabidopsis thaliana. Here, we report the crystal structure of the At-CYP38 protein (residues 83 to 437 of 437 amino acids) at 2.39-Å resolution. The structure reveals two distinct domains: an N-terminal helical bundle and a C-terminal cyclophilin b-barrel, connected by an acidic loop. Two N-terminal b-strands become part of the C-terminal cyclophilin b-barrel, thereby making a previously undiscovered domain organization. This study shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 44 publications
1
69
0
1
Order By: Relevance
“…Crystal structural analysis of CYP38 revealed the presence of N-terminal helical bundle and C-terminal cyclophilin b-sheet domains. This study also uncovered a unique and previously uncharacterized domain, which may provide further understanding of the auto-inhibition mechanism of CYP38 function [36]. There are more than 50 gene models in Chlamydomonas with similarity to immunophilin proteins [75].…”
Section: Regulatory Factors For Psii Assemblymentioning
confidence: 80%
“…Crystal structural analysis of CYP38 revealed the presence of N-terminal helical bundle and C-terminal cyclophilin b-sheet domains. This study also uncovered a unique and previously uncharacterized domain, which may provide further understanding of the auto-inhibition mechanism of CYP38 function [36]. There are more than 50 gene models in Chlamydomonas with similarity to immunophilin proteins [75].…”
Section: Regulatory Factors For Psii Assemblymentioning
confidence: 80%
“…16 CYP38 from Arabidopsis does not exhibit the PPIase activity, however it has been shown to interact with other proteins. 17 The structural analysis of cyclophilin 40 (CyP40) from mammal has revealed that the tetratricopeptide (TPR) protein domain interacts with HSP-90, indicating the crucial role played by these proteins in signaling. 18 Although cyclophilins are ubiquitous proteins, the current study has been restricted to the study of Cyclophilin gene family from two model plant species Rice and Arabidopsis and the model eukaryotic system Yeast.…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast thylakoid lumenal protein AtCYP38 was regarded to contain a leucine-zipper domain at N-terminus of its mature form (He et al 2004 ;Sirpiö et al 2008 ), but X-ray analysis of crystal structure revealed that the N-terminus of AtCYP38 contains a PsbQ-like domain, rather than a leucinezipper domain (Vasudevan et al 2012 ). AtCYP40 contains an N-terminus PPIase domain, a nuclear targeting signal in the middle and three TPR domains at the C-terminus.…”
Section: Arabidopsis Cyclophilinsmentioning
confidence: 99%